Chromosome 22q11 microdeletions in tetralogy of Fallot. Issue 1 (January 1996) - Trainer, A H; Morrison, N; Dunlop, A; Wilson, N; Tolmie, J
Abstract : Chromosome 22q11 fluorescence in situ hybridisation (FISH) studies were performed on 33 consecutive individuals attending a paediatric cardiology clinic with tetralogy of Fallot. Seven children had 22q11 microdeletions but only four had other clinical features associated with the newly recognised chromosome 22 deletion syndrome (CATCH 22). Chromosome 22q11 FISH studies should therefore be performed on all patients with tetralogy of Fallot.